2022
DOI: 10.1177/20503121221102099
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary blood donation practice and its associated factors among civil servants in Bale Robe town, Southeast Ethiopia, 2021

Abstract: Objective: The objective of this study was to assess voluntary blood donation practice and associated factors among Bale Robe town civil servants in Oromia, Southeast Ethiopia, 2021. Methods: An institution-based cross-sectional study was conducted among 601 civil servants selected by a stratified systematic random sampling technique. Data were collected using a structured self-administered questionnaire. The questionnaire was pre-tested on 5% of the total sample size before actual data collection. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The results of this study also revealed that 299 (70.85%) (Cl 66.3–75.1%) of the participants had never given blood in their lives. This study finding is comparable to that of Bale Robe town (73%) ( 17 ), higher than that of Hong Kong 50.5% ( 18 ), and lower than that of Harar town 77.4% ( 14 ), Gonder town 81.6% ( 14 ), Birbir town 89.4% ( 16 ), Debre Markos town (83.9%) ( 7 ), and Adama town 83% ( 6 ). The WHO advises that all nations obtain their blood from consenting blood donors ( 19 ).…”
Section: Discussionsupporting
confidence: 64%
“…The results of this study also revealed that 299 (70.85%) (Cl 66.3–75.1%) of the participants had never given blood in their lives. This study finding is comparable to that of Bale Robe town (73%) ( 17 ), higher than that of Hong Kong 50.5% ( 18 ), and lower than that of Harar town 77.4% ( 14 ), Gonder town 81.6% ( 14 ), Birbir town 89.4% ( 16 ), Debre Markos town (83.9%) ( 7 ), and Adama town 83% ( 6 ). The WHO advises that all nations obtain their blood from consenting blood donors ( 19 ).…”
Section: Discussionsupporting
confidence: 64%
“…Regarding the practice of voluntary blood donation, 105 (71.4% and 29% among those donated and among the total participants respectively) were volunteers, which is comparable with the study conducted in Bale. 27 , 39 However, this result is higher than 10.6% voluntary blood donation practice in Birbir town, 18 16.8% voluntary practice in Bahir Dar, 37 and 63.7% in Debre Markos’ study. 35 The increment in this study could be due to the awareness creation and mobilization activities done in the University in collaboration with Nekemte blood bank.…”
Section: Discussionmentioning
confidence: 77%
“…This is in agreement with the study conducted in Bale Robe town. 27 The possible reason to this association is that taking part in blood donation campaign can make the students aware about the importance of blood donation. In turn, it might increase the students’ motivation to donate blood.…”
Section: Discussionmentioning
confidence: 99%
“…The results were slightly higher than those of studies conducted in Chiro town of Eastern Ethiopia and lower than those of studies conducted among students at Madda Walabu University and Bale Robe town in Southeast Ethiopia. 28 , 33 , 34 This discrepancy might be due to differences in the study population and sociodemographic factors, suggesting that willingness to donate blood is a crucial variable that significantly influences practices related to blood donation.…”
Section: Discussionmentioning
confidence: 97%
“…After identifying cases and controls that means who had blood donation practices and non-donors at each hospital proportional allocation of cases and controls were done. The cases and controls of each hospital were TGSH (49,147), FHCSH (63,189) and AAH 11 , 28 respectively. Finally, cases and controls were selected by using simple random sampling technique by using random number table in each selected facility.…”
Section: Methodsmentioning
confidence: 99%